Evaluating the Decision to Implement Fully Automated Testing to Increase Business Quality Service in Asuransi Astra Digital Products - Sachi Hongo; Yos Sunitiyoso (PT Mattawang Mediatama Solution, 2024)
Taking these developments into account, this research will focus on assessing the ability of Asuransi Astra's digital teams to implement a fully automated testing process for its digital products. By analyzing various factors that can influence the successful implementation of automated testing, this research aims to provide insights in determining what and how many features requires to be selected to be tested by automation within Asuransi Astra's digital products. The aim of this research is to evaluate the discision to implement fully automated testing to increase bussines quality services in asuransi astra digital products. After determining the research design, the author requires data to assist in answering the research questions and achieving the goals. There is a process known as data collection for gathering necessary data. The model has facilitated understanding role expectations and aligned team efforts, allowing for a more synchronized approach towards teamwork and strategy.